FROM THE HISTORY OF CULTURAL RELATIONS BETWEEN UZBEKISTAN AND INDIA - Behruz Sayfullaev (International Scientific and Current Research Conferences, 2021)
Along with political, trade and economic relations between Uzbekistan and India cultural ties are developing on a new page. This article analyzes the cultural aspects of bilateral relations from a historical point of view.